Extraction of tannin from Abrus precetorius seed in leather processing: An eco-friendly approach - Md. Abul Hashem; Md. Shahriar Shahadat; Jannatul Nime Tabassum; Md. Mukimujjaman Miem; Modinatul Maoya (Green Technologies and Sustainability)
Retanning is a significant process in leather manufacturing to improve physicomechanical properties based on the desired characteristics of the final leather. To ensure a sustainable environment, an eco-friendly tanning agent is used in retanning process instead of mineral tannin e.g. chromium. This study reveals the usage of an alternative vegetable tanning agent from Abrus precetorius (Rosary pea) and compares the characteristics with chromed retanned leathers. The extracted tannin through solvent extraction was characterized by Fourier Transform Infrared (FTIR) spectroscopy, which indicates the presence of the functional group, responsible for tanning. Scanning Electron Microscopy (SEM) demonstrated the surface morphology of conventional and experimental crust leather. The tannin content in the seed of Abrus precetorius was found to be 15.34 %. The tensile strength (298.8 kg/cm 2), rate of elongation (74.2%), grain crack load (40.2 kg), strength at ball burst (53.7 kg), shrinkage temperature (108.8 °C) and distention during grain crack and ball burst (7.8 mm and 8.8 mm) of experimental leather meet the desired requirements. This investigation introduces an innovative potential replacement of chromium which propagates the use of novel vegetable tanning agents to make the green leather industry which can reduce the pollution load.